PEMIJAHAN IKAN BETOK (Anabas testudineus) DALAM KOLAM TERPAL DENGAN KETINGGIAN AIR BERBEDA - Muslim Muslim; Mirna Fitrani; Muhammad Busroh (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2019)
Cimbing perch fish is one of the prospective species to be developed into anaquaculture commodity.The purposes of this study was to determine the performance of the results of spawning of climbing perch fish in tarpaulin with different water levels. The study was conducted at the Aquaculture Laboratory, Aquaculture Study Program, Faculty of Agriculture, Sriwijaya University, Indralaya. The study design used a completely randomized design, three treatments, three replications. The treatment is different water levels: P1 (16 cm), P2 (28 cm), P3 (40 cm). The results showed that different water levels had a significant effect on latent time, number of eggs and survival of larvae (D0 - D3) of climbing perch fish.The study showed that the treatment of P3 (40 cm) gave the fastest latency time, which was 16,077 minutes, 4,347 eggs spawned and the percentage of survival of larvae (D0-D3) 88.82%. Conclusion, the best water level for spawning climbing perch in a tarpaulin pond is 40 cm.